Integrating Sumbang Duo Baleh Values into Early Childhood Character Education through Interactive Google Sites Media - Warmansyah, Jhoni; Sari, Meliana; Zalzabila, Zakiah; Yulia, Nova; Siregar, Rahayu Yandira; Wiliani, Sherly (Ta'dib, 2024)
Character education in early childhood is crucial for shaping behavior and morals, especially by integrating local cultural values. This study develops interactive Google Sites media to teach Sumbang Duo Baleh character values to children aged 5-6, using the Research and Development (R&D) method with the 4D model. Validated by education and technology experts, the media achieved a "Highly Valid" rating with a 95.31% content feasibility score and 87.96 for media presentation in functionality, usability, efficiency, and portability. It was also rated highly practical, scoring 85.7 for ease of use by teachers in daily activities. Integrating Sumbang Duo Baleh values into interactive media offers an effective strategy for enhancing character education and fostering culturally relevant learning in Indonesian early childhood education.